2015
DOI: 10.1007/s00421-015-3143-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeated muscle damage blunts the increase in heat strain during subsequent exercise heat stress

Abstract: 2 ABSTRACTPurpose: Exercise-induced muscle-damage (EIMD) has recently been shown to increase heat strain during exercise-heat-stress (HS), and represents a risk factor for exertional heat illness (EHI). We hypothesised that a repeated-bout of EIMD blunts the increase in rectal temperature (Tre) during subsequent endurance exercise in the heat. Methods: Sixteen non-heat-acclimated males were randomly allocated to EIMD (n=9) or control (CON, n=7). EIMD performed a downhill running treatment at -10% gradient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
1
15
1
1
Order By: Relevance
“…Byrnes et al [193] reported smaller increases in plasma CK, plasma myoglobin and DOMS up to 48 h after a second DR bout when two 30 min bouts (slope: − 10%; intensity: 170 beats min −1 of heart rate recorded on level grade) were separated by 3-, 6-and 9-weeks. Further studies corroborated these results by reporting a lower leakage and/ or a faster clearance of intracellular muscle proteins in the blood [46,63,67,85,92,121,141,143,165,181,185], lower DOMS [63,68,85,92,121,141,143,185,192,196,197] and enhanced recovery of MVC force/torque [63] after a second DR bout (Table 1 and Fig. 3b).…”
Section: Prior Exposure To Downhill Runningsupporting
confidence: 60%
“…Byrnes et al [193] reported smaller increases in plasma CK, plasma myoglobin and DOMS up to 48 h after a second DR bout when two 30 min bouts (slope: − 10%; intensity: 170 beats min −1 of heart rate recorded on level grade) were separated by 3-, 6-and 9-weeks. Further studies corroborated these results by reporting a lower leakage and/ or a faster clearance of intracellular muscle proteins in the blood [46,63,67,85,92,121,141,143,165,181,185], lower DOMS [63,68,85,92,121,141,143,185,192,196,197] and enhanced recovery of MVC force/torque [63] after a second DR bout (Table 1 and Fig. 3b).…”
Section: Prior Exposure To Downhill Runningsupporting
confidence: 60%
“…The current study also observed a reduction in thermal strain (T re −0.3°C) equivalent to that of various heat acclimation regimes (Gibson et al, 2015b; Tyler et al, 2016), and an attenuated perceived muscle soreness (24 h post = +12.2%, 48 h post = −16.5%) response that is indicative of muscle damage (Fridén et al, 1981) from near identical exercise trials [HPC2 HOTDOWN compared to HPC1 HOTDOWN (see Figure 2 and Table 3)]. Together these responses indicate that downhill running models may be able to elicit a beneficial preconditioning effect (Dolci et al, 2015; Tuttle et al, 2015). Given that acute non-damaging exercise heat stress does not improve thermal responses to a greater extent than equivalent temperate condition exercise [Figure 2, (Lee et al, 2014)], the cellular responses to the eccentric muscle action of the damaging downhill running is important.…”
Section: Discussionmentioning
confidence: 94%
“… 38 In addition to heat stress inducing a GI protective effect, exercise-induced muscle damage (EIMD) has also been shown to blunt heat strain whereby subjects exposed to both exercise heat stress and EIMD up to 14 days after the initial exposure, showed attenuated rises in core temperature and a reduced threshold for the initiation of sweating. 39 These studies indicate that acute heat stress can provide some protection against GI permeability and counteract the leakage of LPS into the internal environment. This protection is likely related to the favorable alterations in heat shock proteins (HSP), 40 which can thereby minimise the otherwise associated inflammatory response.…”
Section: Gi Dysfunction In Exercise Heat Stressmentioning
confidence: 94%